Dollar exchange rate variability and agricultural policy: consequences on world agricultural prices with reference to Aargentina - Colome, Rinaldo (1988)
The purpose of this paper is to analyze the consequences of dollar real exchange rate changes in agricultural markets with special reference to Argentina. This is done under different assumptions concerning exchange rate policies for Argentina and other countries involved, and also under different assumptions on market structure. Another main interest is also to know how U.S, agricultural and trade policies influence the markets in which Argentina sells its products.